CAPITAL ASSET PRICING MODEL (CAPM) SEBAGAI ALAT ANALISIS DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA INDEKS LQ-45 DI BURSA EFEK INDONESIA (BEI) PERIODE AGUSTUS 2020 – JANUARI 2021 - Aprialinita, Dhea; Waldeska Aulia, Fezi; Dwi Aristi, Mentari; Hikmah Putri, Nurul; Nurliyana, Nurliyana; Putri Permatasari, Vina; Sari, Juita (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study aims to assist investors in making stock investment decisions on the LQ-45 index for the period August 2020 - January 2021 using the Capital Asset Pricing Model (CAPM). The population of this study is all stocks listed on the Indonesia Stock Exchange (IDX), the sample in this study is 45 companies listed on LQ-45 for the period August 2020-January 2021. This type of research is descriptive research with a quantitative approach. The data collection technique used is documentation. Meanwhile, the data analysis technique uses the Capital Asset Pricing Model (CAPM). The results of this study indicate that there are 31 companies that are classified as efficient and 14 companies that are classified as inefficient.